2019
DOI: 10.1016/j.abrep.2018.100149
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in retail marketing for little cigars and cigarillos in Los Angeles, California

Abstract: Introduction Evidence of a concentration of cigarette advertising in predominantly low-income, non-White neighborhoods underscores the need to examine retail marketing and promotions for novel tobacco products like little cigars and cigarillos (LCCs). We sought to investigate neighborhood racial/ethnic disparities in LCC marketing at retail, including availability, advertising, price promotions, and product placement in Los Angeles, California. Methods Between January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 31 publications
7
27
1
Order By: Relevance
“…Greater e-cigarette availability in NHW communities may be explained by higher use, awareness and positive perceptions among community members, which may lead to increased customer demand. Within the context of other emerging tobacco products, current findings differ from previous research which found that retailers within non-white communities were more likely to sell and advertise little cigars and cigarillos 13…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Greater e-cigarette availability in NHW communities may be explained by higher use, awareness and positive perceptions among community members, which may lead to increased customer demand. Within the context of other emerging tobacco products, current findings differ from previous research which found that retailers within non-white communities were more likely to sell and advertise little cigars and cigarillos 13…”
Section: Discussioncontrasting
confidence: 99%
“…Identifying tobacco retailers on AI Tribal land required a unique strategy as federally recognised tribes are sovereign nations and retailers are not required to obtain state licensure to sell tobacco products 12 13. Stores on Tribal land were identified in Southern, Central and Northern California using Google Maps, Esri Business Analyst data and store listings provided by CDTFA 12 13. The number of tobacco retailers varied across Tribal lands; therefore, all stores on Tribal land or within a 1-mile radius were included in the sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The affordability of cigarillos encourages Black young adults to maintain and increase cigar smoking even when experiencing economic losses during the pandemic. Much evidence has already shown that these targeted marketing tactics have contributed to the disproportionately high use of cigarillo products among Black communities ( Cantrell et al, 2013 , Smiley et al, 2019 ). Therefore, local-level tobacco regulations, including increased cigar minimal pricing, restrictions on price promotions, and reduced tobacco retailer density are greatly needed to minimize the influence of pervasive and targeted marketing to reduce cigar smoking-caused disparities among Black communities.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to retail tobacco marketing is a risk factor for smoking initiation among adolescents (12,13) and increased smoking among adults (9,14). The literature (15)(16)(17) on tobacco marketing disparities in the retail environment is growing, and findings indicate that low-income and majority non-White neighborhoods have high densities of tobacco retailers and are disproportionately exposed to marketing of cheap, harmful, combustible tobacco products, including menthol cigarettes.…”
Section: Introductionmentioning
confidence: 99%